2020
DOI: 10.1107/s2056989019016268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of catena-poly[[bis[(2,2′;6′,2′′-terpyridine)manganese(II)]-μ4-pentathiodiantimonato] tetrahydrate] showing a 1D MnSbS network

Abstract: The asymmetric unit of the title compound, {[Mn2Sb2S5(C15H11N3)2]·4H2O} n , consists of two crystallographically independent MnII ions, two unique terpyridine ligands, one [Sb2S5]4− anion and four solvent water molecules, all of which are located in general positions. The [Sb2S5]4− anion consists of two SbS3 units that share common corners. Each of the MnII ions is fivefold coordinated by two symmetry-related S atoms of [Sb2S5]4− anions and three N atoms of a terpyridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Most of these compounds were synthesized by solvothermal reactions using the elements as reactands, which is a disadvantage for several reasons. Recently, we have found that many such compounds are more easily available if simple metal salts such as, for example, Schlippe's salt (Na 3 SbS 4 Á9H 2 O) or NaSbS 3 are used as starting materials (Anderer et al, 2014(Anderer et al, , 2016Danker et al, 2020). The major advantage of this approach is the fact that different SbS x species are present in solution, which in some cases allows the preparation of thioantimonates already at room temperature.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Most of these compounds were synthesized by solvothermal reactions using the elements as reactands, which is a disadvantage for several reasons. Recently, we have found that many such compounds are more easily available if simple metal salts such as, for example, Schlippe's salt (Na 3 SbS 4 Á9H 2 O) or NaSbS 3 are used as starting materials (Anderer et al, 2014(Anderer et al, , 2016Danker et al, 2020). The major advantage of this approach is the fact that different SbS x species are present in solution, which in some cases allows the preparation of thioantimonates already at room temperature.…”
Section: Chemical Contextmentioning
confidence: 99%
“…An increase of the S–Mn–S angle to 103.7° leads to even shorter Mn–S bonds with 2.442 and 2.501 Å . In the structure of the recently published compound {[Mn 2 (terpy) 2 Sb 2 S 5 ] · 4H 2 O} n a one dimensional chain is observed consisting of Mn 2 Sb 2 S 4 rings which are interconnected by S 2– anions. Like in the structure of the title compound, the unique Mn 2+ cations are in a strongly distorted environment of three N atoms of the terpy ligand and two S 2– anions of SbS 3 3– pyramids, reminiscent to that of the polyhedron observed in I .…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, we have explored such compounds over many years (Schaefer et al, 2003;Sta ¨hler et al, 2001;Schur et al, 1998Schur et al, , 2001Kiebach et al, 2004;Spetzler et al, 2004;Lu ¨hmann et al, 2008;Pienack et al, 2008b). In the beginning, we synthesized new thioantimonates using elemental antimony, sulfur and amine molecules under solvothermal conditions but later we found that ISSN 2056-9890 many of these compounds are also available under solvothermal conditions if Schlippesches salt (Na 3 SbS 4 Á9H 2 O) or NaSbS 3 are used as reactants (Anderer et al, 2014(Anderer et al, , 2016Danker et al, 2020). In this case, different SbS x species are present in solution, because Schlippesches salt is unstable and forms different reactive species such as [SbS 3 O] 3À , HS À , [S 2 O 3 ] 2À or [SbS 4 ] 3À anions (Rammelsberg, 1841;Long & Bowen, 1970;Mosselmanns et al, 2000;Planer-Friedrich & Scheinost, 2011;Planer-Friedrich & Wilson, 2012;Anderer et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%